2007
DOI: 10.3171/spi-07/08/124
|View full text |Cite
|
Sign up to set email alerts
|

Dysphonia and dysphagia after anterior cervical decompression

Abstract: Object. In this paper, the authors investigate the effects of anterior cervical decompression (ACD) on swallowing and vocal function. Methods. The study comprised 114 patients who underwent ACD. The early group (50 patients) was examined immediately pre- and postoperatively, and the late group (64 patients) was examined at only 3 to 9 months postoperatively. Fifty age- and sex-matched patients from the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 27 publications
2
37
0
3
Order By: Relevance
“…2,5,6,9,10,12,16,18,21,22,[27][28][29]31,32 However, the associations are not consistent among studies.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…2,5,6,9,10,12,16,18,21,22,[27][28][29]31,32 However, the associations are not consistent among studies.…”
mentioning
confidence: 79%
“…Fortunately, most studies show dysphagia to be typically a transient phenomenon following anterior cervical surgery. 2,22,31 The pathophysiology of dysphagia following cervical spine surgery remains poorly understood. Several factors have been suggested to be related to the development of postsurgical dysphagia, including patient age, female sex, obesity, length of surgery, specific spinal level(s) of surgery, multilevel surgery, use of instrumen- Object.…”
mentioning
confidence: 99%
“…Other studies suggest, however, that these interventions have no effect on postoperative dysphagia [3,23]. Various intraoperative and patient factors (ie, age, gender, body mass index, operative time, estimated blood loss, number of levels of surgery, location of surgery, and plate thickness) have been investigated as potential risk factors for postoperative dysphagia with inconsistent findings [4,7,17,18,23,27,29]. Fortunately, postoperative dysphagia is typically a transient phenomenon.…”
Section: Introductionmentioning
confidence: 98%
“…Generally speaking, these procedures provide return to function and pain relief and a low incidence of major complications [1,10,14,19,21,22,25,26]. The most common patient complaint after this procedure is dysphagia; the reported incidence of which is up to 69% in the early postoperative period [12,29,30]. The proposed causes of postoperative dysphagia include recurrent laryngeal nerve palsy, esophageal ischemia and reperfusion injury, and local soft tissue swelling.…”
Section: Introductionmentioning
confidence: 98%
“…27 This may be due to damage or insult to the vagus nerve (the recurrent laryngeal nerve) and/or distension or soft tissue swelling, which can be associated with the surgery. Tervonen et al 28 reported that 69% of patients with anterior cervical surgeries had dysphagia immediately post-operatively (within the first week); however, after 3 months, most dysphagia had resolved. Several issues may contribute to SLPs spending more time evaluating and treating swallowing deficits than cognitive-communication problems.…”
Section: Slp Servicesmentioning
confidence: 99%